Stick-Slip Transition Behaviour of Two High Density Polyethylene Melts on Capillary Rheometer - Hua-Yong, Liao; Lu-Yao, Zheng; Yong-Bing, Hu; Xian-Jun, Zha; Xiang, Xu; Yan-Wei, Wen (Journal of Research Updates in Polymer Science, 2014)
The stick-slip transition behaviour of two high density polyethylene (HDPE) melts are studied experimentally by using a capillary rheometer with twin bores at different temperatures. The shear stress-shear rate curves are investigated by the capillary rheometer with two diameters. The results show that the flow curves break at a certain critical shear stress. The broken point of the flow curve implies the occurrence of the stick-slip transition. The critical shear stresses obtained by the two capillaries equal approximately, but extrapolation slip length increases with the diameter of the capillary. It is found that the critical shear stress increases proportionally with absolute temperature, which means increasing temperature can depress or delay the occurrence of slippage to a certain degree. Additionally it is found the slip section’s slope of the shear stress-shear rate curve is lower than the sticky section’s slope.